The Impact of Corruption on Economic Stability and Community Life in Indonesia - Annisa, Neng Nur; Lavides, Maria Margarita R. (Department of Public Administration, 2025)
This study aims to analyze the social and economic impact of corruption in Indonesia. Using the thematic method, statements of key personalities and data gathered from documentation studies were analyzed. Results of data analysis revealed that corrupt practices inhibit economic progress and erode public trust. Moreover, it promotes a negative perception on state institutions, unjust distribution of resources, and unsatisfactory public goods and services. Corruption has a direct impact on vital sectors such as education, health, and economic development, thus hindering the improvement of the quality of human resources and community welfare. Prevalence of corruption exacerbates social inequality and violations of human rights. Eradicating corruption requires collaborative efforts among various stakeholders as well as improvement on the enforcement and public awareness of the law.